Caminhos da fé: arranjos socioespaciais (re)criados pelos(as) romeiros(as) de Nossa Senhora D'Abadia na MG-190 - Macedo, Patrícia Gomes (2024)
In this thesis, the pilgrimage is understood as an informal, cyclical, and supportive socioterritorial practice, originating in popular Catholicism and relatively autonomous in relation to the Catholic Church. It results from the collective and anonymous work of the pilgrims, non-specialized agents in religion, and manifests itself through spatial movements, social and religious practices, and the use and appropriation of space. This process redefines spatial forms and contents, establishing bonds and belonging to places to fulfill religious commitments. Inserted in the Geography of Religion, the research explores the interactions between religious phenomena and geographic space, engaging with humanistic, cultural, and critical approaches to present a comprehensive analysis of the religious phenomenon. The main objective was to investigate the role of places in sustaining and continuing the pilgrimage, analyzing how the interactions between space and individuals generate forms of appropriation linked to religious commitment. The research focused on verifying the hypothesis that the pilgrims, through their interactions and use of space along MG-190, promote changes in the original forms and meanings attributed to space. These transformations result in practices, symbolic representations, and commitments of faith. To this end, a mixed-methods approach was adopted, using qualitative methods (fieldwork, autoethnography, and interviews) and quantitative methods (questionnaire). The data were organized and categorized according to Content Analysis and interpreted in light of the Historical Structural Dialectical Method. By integrating theoretical analysis with empirical data, the initial hypothesis was confirmed. It is concluded that the integration of different geographical approaches allows for a more complete and multifaceted understanding of the interactions between religion and space, contributing to the advancement of the Geography of Religion and offering new theoretical and methodological perspectives.